PERTANGGUNGJAWABAN HUKUM NOTARIS PENGGANTI SETELAH BERAKHIR DALAM MENJALANKAN TUGAS JABATANNYA - MIFTAHUL HUSNA (PREMISE LAW JURNAL, 2017)
A substituted Notary is a person who is temporarily appointed as a Notary to substitute a Notary who is on leave, sick, or temporarily involuntarily absent. The requirement for appointing substitute Notary is different from the actual Notary, but his task and responsibility are the same as that of an actual Notary. The research used juridical normative and descriptive analytic method, supported by interviews. The data were gathered by conducting library research and documentary study and analyzed qualitatively by describing them in the form of sentences and drawing conclusion. Theconclusion of the research was that, based onArticle 65 of Law No. 2/2014 on Notarial Position, a substitute Notaryis liable for every deed he has made even though Notarial Protocol has been submitted to the person in charge of Notarial Protocol. It means that substitute Notary is always liable for the deeds he has made although his tenure ends. Keywords : Liability of Substitute Notary, the End of Tenure